2022
DOI: 10.1002/advs.202202216
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between DNMT1 and High‐Mannose CD133 Maintains the Slow‐Cycling State and Tumorigenic Potential of Glioma Stem Cell

Abstract: The quiescent/slow‐cycling state preserves the self‐renewal capacity of cancer stem cells (CSCs) and leads to the therapy resistance of CSCs. The mechanisms maintaining CSCs quiescence remain largely unknown. Here, it is demonstrated that lower expression of MAN1A1 in glioma stem cell (GSC) resulted in the formation of high‐mannose type N‐glycan on CD133. Furthermore, the high‐mannose type N‐glycan of CD133 is necessary for its interaction with DNMT1. Activation of p21 and p27 by the CD133–DNMT1 interaction ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…CSCs are a small subpopulation of quiescent cells with self-renewal abilities and pluripotency that can drive tumor initiation and cause relapses [7]. CSCs generate the bulk of tumors via their self-renewal and their ability to differentiate into multiple cellular subtypes [8].…”
Section: Introductionmentioning
confidence: 99%
“…CSCs are a small subpopulation of quiescent cells with self-renewal abilities and pluripotency that can drive tumor initiation and cause relapses [7]. CSCs generate the bulk of tumors via their self-renewal and their ability to differentiate into multiple cellular subtypes [8].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that differential N-glycosylation of CD133 extracellular domain among tumor sub-populations may be related to specific functions, subcellular localization, and turnover. In line with this, Wei et al (2022) reported that CD133 C-terminal domain interaction with DNMT1 (DNA methyltransferase 1) depends on CD133 glycosylation status in glioma stem-like cells (GSCs) [ 24 ]. High-mannose CD133 maintains GSCs in a slow-cycling state (quiescence) by blocking DNMT1 nuclear translocation.…”
Section: Cd133: Structure Localization and Posttranslational Modifica...mentioning
confidence: 98%
“…Interestingly, the glycosyltransferase 8 domain containing 1 (GLT8D1) was recently shown to contribute to the stabilization of CD133 by interacting with it and influencing its glycosylation in glioma cells [ 157 ]. Similarly, the interaction of the high-mannose N-glycan form of CD133 with cytoplasmic DNA methyltransferase 1 (DNMT1) maintains the slow-cycling state of glioma stem cells, and favors chemotherapy resistance and tumorigenesis [ 158 ]. These observations are in line with the differential glycosylation status of CD133 in relation to cell differentiation [ 7 , 11 ].…”
Section: Molecular Biology Of Cd133mentioning
confidence: 99%